ANALYTICAL LABORATORY RESULTS OF CONTINUOUS CONTROL OF DRINKING WATER QUALITY AND WASTEWATER TREATMENT - Alibekova Nazira Nazarovna (Scholar Express Journal, 2022)
Analytical laboratories for the control of drinking water and wastewater treatment actually perform the functions of product quality control departments in the field of water supply and sewerage.
Keywords: Drinking water; water supply; microbiological composition; water supply networks